Roles of Ca2+/calmodulin-dependent protein kinase II in subcellular expression of striatal N-Methyl-D-aspartate receptors in L-3, 4-dihydroxyphenylalanine-induced dyskinetic rats - Gan J; Qi C; Liu Z (Dove Medical Press, 2015)
Jing Gan, Chen Qi, Zhenguo LiuDepartment of Neurology, Xinhua Hospital affiliated to Shanghai Jiao Tong University Medical School, Shanghai, People’s Republic of ChinaBackground: The role of N-Methyl-D-aspartate (NMDA) receptors is critical to the development of l-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesia (LID) in Parkinson’s disease (PD). Ca2+/calmodulin-dependent protein kinase II (CaMKII) is thought to regulate the expression and activation of NMDA receptors in LID, but the interaction between LID and CaMKII-modulated NMDA receptor activity is not clear so far.Methods: We used 6-hydroxydopamine-lesioned rats to create PD rat model, and at least 21 days of L-DOPA was administrated followed with or without microinjection of CaMKII inhibitor KN-93 into the lesioned striatum of all the PD rats and sham rats. A surface receptor cross-linking assay was used to distinguish expression of striatal NMDA receptors in surface and intracellular compartments.Results: L-DOPA treatment enhanced surface levels of GluN1 expression and reduced its intracellular expression, but did not change total levels of GluN1 protein in the lesioned striatum. In contrast, L-DOPA decreased GluN2A surface expression but increased its intracellular expression. L-DOPA increased GluN2B expression preferentially in the surface compartment. We also found that L-DOPA increased CaMKII autophosphorylation at T286 in striatal neurons. The inhibition of CaMKII by microinjecting CaMKII inhibitor KN-93 into the lesioned striatum largely reversed the L-DOPA-induced changes in three subunits. In addition, dyskinetic behaviors of animals were observed alleviated after treatment of KN-93.Conclusion: Our research indicates that long-term L-DOPA administration activates CaMKII in striatal neurons. Activated CaMKII is involved at least in part in mediating L-DOPA-induced changes of NMDA receptors surface/intracellular expression.Keywords: glutamate, GluN1, GluN2A, GluN2B, dopamine, KN-93